Fewer REBOA complications with smaller devices and partial occlusion: evidence from a multicentre registry in Japan. Issue 12 (31st August 2017) - Matsumura, Yosuke; Matsumoto, Junichi; Kondo, Hiroshi; Idoguchi, Koji; Ishida, Tokiya; Kon, Yuri; Tomita, Keisuke; Ishida, Kenichiro; Hirose, Tomoya; Umakoshi, Kensuke; Funabiki, Tomohiro
Abstract : Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) performed by emergency physicians has been gaining acceptance as a less invasive technique than resuscitative thoracotomy. Objective: To evaluate access-related complications and duration of occlusions during REBOA. Methods: Patients with haemorrhagic shock requiring REBOA, from 18 hospitals in Japan, included in the DIRECT-IABO Registry were studied. REBOA-related characteristics were compared between non-survivors and survivors at 24 hours. 24-Hour survivors were categorised into groups with small (≤8 Fr), large (≥9 Fr) or unusual sheaths (oversized or multiple) to assess the relationship between the sheath size and complications. Haemodynamic response, occlusion duration and outcomes were compared between groups with partial and complete REBOA. Results: Between August 2011 and December 2015, 142 adults undergoing REBOA were analysed. REBOA procedures were predominantly (94%) performed by emergency medicine (EM) physicians. The median duration of the small sheath (n=53) was 19 hours compared with 7.5 hours for the larger sheaths (P=0.025). Smaller sheaths were more likely to be removed using external manual compression (96% vs 45%, P<0.001). One case of a common femoral artery thrombus (large group) and two cases of amputation (unusual group) were identified. Partial REBOA was carried out in more cases (n=78) and resulted in a better haemodynamic response than complete REBOA (improvement in haemodynamics, 92% vs 70%, P=0.004; achievement of stability, 78% vs 51%, P=0.007) and allowed longer occlusion duration (median 58 vs 33 min, P=0.041). No statistically significant difference in 24-hour or 30-day survival was found between partial and complete REBOA. Conclusion: In Japan, EM physicians undertake the majority of REBOA procedures. Smaller sheaths appear to have fewer complications despite relatively prolonged placement and require external compression on removal. Although REBOA is a rarely performed procedure, partial REBOA, which may extend the occlusion duration without a reduction in survival, is used more commonly in Japan.